Dari “Diislamkan” ke “Dipestakan”: Pergeseran Makna Mujêlisên (Khitanan) pada Masyarakat Gayo - Indra Setia Bakti; Harinawati Harinawati; Siti Ikramatoun (Jurnal Sosiologi Agama Indonesia (JSAI), 2021)
This study aims to describe the meaning shift of mujêlisên in Gayo society. The meaning given to the mujêlisên tradition has not been constant at all times. In the Gayo lens traditional, mujêlisên means something Islamic or "to be Islamic". So the activities carried out are directed at actions that are nuanced with spirituality. The study was qualitative research. This study found that over time, the meaning of the mujêlisên tradition was shifted. In praxis, the spirituality aspect not dominates the discourse but has been covered by profane culture festivity practices. It is supported by the various easily accessible facilities to fulfil the consumptive desires of festivity actors.